Investigation of the Polycrystalline Silicon PV Cell Efficiency in 3D Approximation versus Electromagnetic Field under Monochromatic Illumination - Adama Ouedraogo; Boubacar Soro; Ramatou Konate; Fati Amadou Oumarou; Dieudonné Joseph Bathiebo (International Journal of Photoenergy)
This manuscript is about the electric output of the silicon (Si) photovoltaic (PV) cell versus the electromagnetic field of a radio wave and a monochromatic illumination in three-dimensional (3D) assumptions. The polarisation direction of the electromagnetic wave and power density are fixed. The electromagnetic wave is provided by electromagnetic emission sources such as the telecommunication, radio, or TV antennas. A PV system is installed in the vicinity of an electromagnetic emission source. The current produced by the PV cell is sensitive to electromagnetic field increase more than the electric voltage. The electromagnetic field causes the decomposition of the current into two components which are a transferred current and a leakage current. The transferred component provides the transmitted current to the external load while the leakage component gives the loss of the carrier charge into the junction. Consequently, this decomposition of the current shares the electric power in transferred electric power and leakage electric power. The transferred electric power is obtained only in the intermediate circuit, and the maximum power point (MPP) shifts to the short circuit situation as the junction dynamic velocity becomes the greatest. However, the leakage electric power corresponds to a loss of the minority carrier’s charge in the junction during the crossing of the junction. This loss causes a Joule heating effect of the junction. The heating of the junction causes the quality degradation of the PV cell mainly due to the electric component. The solar illumination wavelength is presenting the inversion phenomenon with the maximum of the electrical outputs of the silicon PV cell of around 0.70 μm which provides the greatest conversion efficiency. This value has been chosen for the modelling of the radio wave influence. Hence, the conversion efficiency increases when the PV system is far away from the electromagnetic emission source. PV system installation in the vicinity of an electromagnetic emission source is not advised.